Compound real options valuation of renewable energy projects: The case of a wind farm in Serbia. (August 2017) - Loncar, Dragan; Milovanovic, Ivan; Rakic, Biljana; Radjenovic, Tamara
Abstract: Renewable energy sources have become a very important issue due to environmental and sustainability concerns. In addition, most renewable energy electricity generation (RES-E) projects are characterized by considerable uncertainty and sequential decision-making. These projects' net present value (NPV) is very often close to zero, which renders them a good candidate for the application of real options valuation methodology of investment project appraisal. This paper examines the real options valuation of a potential onshore wind farm project in Serbia. The binomial tree model spans a 15 year period consisting of a 2 year investment period and a 13 year operating period, the first 12 years of which are protected by Feed-in-Tariffs according to local renewable energy regulations. The authors examine a multi-phased compound (nested) path-dependent real option consisting of mutually exclusive options - a sequential option to invest as well as expand, repower, contract and abandon options. Volatility, which is calculated by means of a Monte Carlo simulation according to the logarithmic-present-value-returns approach, shows predominant sensitivity to the capacity factor simulated with the rescaled Weibull's probability distribution. The final binomial tree results show that the proposed sequence of options increases project value by transforming higher risk and lower return in the initial discounted cash flow model, to lower risk and higher return in the RO model. This paper contributes to the existing literature in at least two ways: it presents in-depth analysis of the real option application to the RES-E project and provides decision-makers with sophisticated tool for improving strategic thinking, capital budgeting and decision-making processes.